Pengaruh Penggunaan Augmented Reality Berbantuan Assemblr Edu Dalam Pembelajaran Fisika Pada Materi Perubahan Iklim Terhadap Pemahaman Konsep Siswa - Hidayah, Nur; Nasar , Adrianus; Umbu Kaleka, Melkyanus B. (PendIPA Journal of Science Education, 2025)
This study aims to evaluate the impact of using Augmented Reality (AR) through the Assemblr Edu application on students' understanding of physics concepts, particularly on the topic of climate change. This study employed a quasi-experimental design with a quantitative approach and a posttest-only control design. The population was all eight classes of SMP Negeri 1 Ende in the 2025/2026 academic year. The sample consisted of two classes: class VIII F, the experimental class taught using the experimental method, and class VIII D, the control class taught using the conventional method, with a total of 64 students. The data collection technique used in this study was a test, with a posttest being administered to determine the differences between the control and experimental classes. The data analysis techniques used were descriptive analysis, normality testing, and independent sample t-tests using SPSS 25. The results of the post-test data analysis revealed a significant difference between the average conceptual understanding of students in the experimental class (81.63) and the control class (52.00). The normality test results indicated that the data were normally distributed (Sig. 0.100 > 0.05), allowing for hypothesis testing. The t-test results showed a significance value of <0.001, less than 0.05. Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted.